LÍQUEN PLANO BUCAL E A INFECÇÃO PELO VÍRUS DA HEPATITE C - Barbosa, Hyrlana Leal (2007)
Lichen planus (LP) is a chronic inflammatory disease that affects skin and/or mucous and whose origin still is unknown. In the mouth the disease is called oral lichen planus (OLP). The association between OLP and the hepatitis C virus (HCV) infection has been widely argued in literature with controversial results. The aim of this age- and sex-matched case-control study was evaluate the association between OLP and HCV infection. Thirty individuals with OLP diagnosed in the Reference Center of Oral Disease of the State University of Feira de Santana, comprised of the test group (OLP group), and thirty healthy individuals proceeding from the same population were included in the control group. None out of the OLP group or control group were seropositive for anti-HCV. The results showed there is not association between OLP and HCV infection. Analyses add between the association of the LPB and the presence of systemic diseases, drugs use, menopause and habits to smoke and to consume alcoholic beverage did not shown significance statistics. On the basis of the results of the present study were not possible to establish the association between OLP and HCV infection. In conclusion, further new longitudinal studies may be performed in attempt to clarify this matter.